2008
DOI: 10.1016/j.abb.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Loss of iron–sulfur clusters from biotin synthase as a result of catalysis promotes unfolding and degradation

Abstract: Biotin synthase (BioB) is an S-adenosylmethionine radical enzyme that catalyzes addition of sulfur to dethiobiotin to form the biotin thiophane ring. In vitro, E. coli BioB is active for only one turnover, † This research has been supported by the NIH (R01 GM059175 to J.T.J.) and a fellowship from the David and Lucille Packard Foundation (J.T.J. Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…If not, the protein molecule perishes and must be re-synthesized de novo . More recent work done in vitro has shown that loss of iron-sulfur clusters from BioB as a result of catalysis promotes unfolding and degradation (75). Hence, some BioB molecules may catalyze only one or a few turnovers in their lifetimes whereas others may complete >100 turnovers.…”
Section: The Pathway and Proteins Of Biotin Synthesismentioning
confidence: 99%
“…If not, the protein molecule perishes and must be re-synthesized de novo . More recent work done in vitro has shown that loss of iron-sulfur clusters from BioB as a result of catalysis promotes unfolding and degradation (75). Hence, some BioB molecules may catalyze only one or a few turnovers in their lifetimes whereas others may complete >100 turnovers.…”
Section: The Pathway and Proteins Of Biotin Synthesismentioning
confidence: 99%
“…It described a homologous group of enzymes united by their utilization of SAM in a radical mechanism (Sofia, Chen, Hetzler, Reyes-Spindola, & Miller, 2001). The original sequence set came from 126 species representing all Kingdoms of life and included many of the first RSS enzymes to be characterized: lysine 2,3-aminomutase (LAM), (Moss & Frey, 1987), biotin synthase (BioB) (Lotierzo, Tse Sum Bui, Florentin, Escalettes, & Marquet, 2005; Reyda, Dippold, Dotson, & Jarrett, 2008) lipoyl synthase (LipA) (Cicchillo, Iwig, et al, 2004; Miller et al, 2000), pyruvate-formate lyase activase (PflA) (Knappe & Sawers, 1990; Vey et al, 2008), and anaerobic ribonucleoside-triphosphate reductase activase (NrdG) (Padovani, Thomas, Trautwein, Mulliez, & Fontecave, 2001). From a chemical perspective, to be considered a member of the RSS, Sofia defined three characteristics that were minimally required:…”
Section: Introduction: Overview Of the Radical Sam Superfamilymentioning
confidence: 99%
“…Known functions reveal that RSS enzymes catalyze a dizzying array of disparate and essential chemistries that range from the formation of complex metal cofactors (Dinis, Wieckowski, & Roach, 2016) (e.g. the formation of the [FeFe]-hydrogenase metallocofactor in HydG (Pilet et al, 2009) and HydE (Nicolet et al, 2008)) to the formation of more than half of the over two dozen known organic cofactors (for example, biotin (Lotierzo, Tse Sum Bui, Florentin, Escalettes, & Marquet, 2005; Reyda, Dippold, Dotson, & Jarrett, 2008), lipoic acid (Cicchillo, Lee, et al, 2004; Miller et al, 2000), menaquinone (vitamin K) (Hiratsuka et al, 2008) and pyrroloquinonoline quinone (PQQ) (Barr et al, 2016; Puehringer, Metlitzky, & Schwarzenbacher, 2008)). They are also involved in the modification of nucleic acids, often via methylation of aromatic carbon centers, repair of DNA dimers (as in spore photoproduct lyase (SPL) (Benjdia, Heil, Barends, Carell, & Schlichting, 2012; Yang & Li, 2015)), the formation of the wybutosine base on tRNA (Young & Bandarian, 2011), and the formation of complex natural products such as antibiotics (Mahanta, Hudson, & Mitchell, 2017a, 2017b) (for example nosiheptide (LaMattina et al, 2017; Yu et al, 2009) and bleomycin (Tao et al, 2007)).…”
Section: Introduction: Overview Of the Radical Sam Superfamilymentioning
confidence: 99%
“…In the case of those with labile FeS clusters, their steady state abundance relies on the operation of cluster repair mechanisms, and these are sensitive to Fe availability (Garland et al, 1999;Jensen and Culotta, 2000;Djaman et al, 2004). In Fe deficiency, the apoproteins would not be remetallated, making them susceptible to proteases (Reyda et al, 2008). For other Fe proteins, a recognition mechanism is not obvious, but their degradation might be a consequence of oxidative stress damage from reaction of the active site Fe with H 2 O 2 (Halliwell and Gutteridge, 1984;reviewed in Imlay, 2008).…”
Section: Maintenance Of Fesodmentioning
confidence: 99%